Design and control of large-scale grid-connected photovoltaic power plant with fault ride-through - Al-Shetwi, Ali Qasem Saleh (2019)
Over the recent years, the installation of photovoltaic (PV) system and integration with electrical grid has become more widespread worldwide. With the significant and rapid increase of photovoltaic power plants (PVPPs) penetration to the electric grid, the power system operation and stability issues become crucial and this leads to continuous evaluation of grid interconnection requirements. For this purpose, the modern grid codes (GCs) require a reliable PV generation system that achieves fault ride-through (FRT) requirements. Therefore, the FRT capability becomes the state of art as one of the challenges faced by the integration of large-scale PV power stations into electrical grid that has not been fully investigated. This research proposes FRT requirements for the connection of PVPPs into Malaysian grid as new requirements. In addition, presents a comprehensive control strategy of large-scale PVPPs to enhance the FRT capability based on modern GCs connection requirements. In order to meet these requirements, there are two major issues that should be addressed. The first one is the ac over-current and dc-link over-voltage that may cause disconnection or damage to the grid inverter. The second one is the injection of reactive current to assist the voltage recovery and support the grid to overcome the voltage sag problem. To address the first issue, the dc-chopper brake controller and current limiter are used to absorb the excessive dc-voltage and limits excessive ac current, respectively, and therefore protect the inverter and ride-through the faults smoothly. After guaranteeing that the inverter is kept connected and protected, this control strategy can also ensure a very important aspect which is the reactive power support through the injection of reactive current based on the standard requirements. Feed-forward decoupling strategy based-dq control is used for smooth voltage fluctuation and reactive current injection. Furthermore, to keep the power balance between both sides of the inverter, PV array can generate a possible amount of active power according to the rating of grid inverter and voltage sag depth by operating in two modes, which are normal and FRT modes. These two modes of operation require fast and precise sag detection strategy to switch the system from normal mode to a faulty mode of operation for an efficient FRT control. For this purpose, RMS detection method has been used. In this research, the large-scale PV plant connected to the MV side of the utility grid, taking the compliance of TNB technical regulations for PVPPs into consideration has been modelled using MATLAB/Simulink with nominal rated peak power of 1500 kW. Analyses of the dynamic response for the proposed PVPP under various types of symmetrical and asymmetrical grid faults also had been investigated. As a conclusion, the PVPP connected to the power grid provided with FRT capability has been developed. The sizing of the suggested PV array is achieved in which the simulation results matched the sizing calculation results. Moreover, the results at the point of common coupling show that the proposed PVPP is compatible with TNB requirements, including the PV-grid connection method, PV inverter type, nominal voltage operating range, total harmonic distortion less than 5%, voltage unbalance less than 1%, frequency fluctuation within ± 0.1 Hz, and power factor higher than 0.9. In addition, the control simulation results presented demonstrate the effectiveness of the overall presented FRT control strategy, which aims to improve the capability of ride-through during grid faults safely, to keep the inverter connected, to ensure the safety of the system equipment, to ensure all values return to pre-fault values as soon as the fault is cleared within almost zero second as compared to the strategy without FRT control which needs around 0.25s, and to provide grid support through active and reactive power control at different types of faults based on the FRT standard requirements.